IMMUNODEFICIENCY IN PANCREONECROSIS - V. S. Tarasenko; V. L. Averkiev (Креативная хирургия и онкология, 2017)
In 104 patients who underwent surgery for acute destructive pancreatitis there was reviled immunological malfunction when different phases of disease. Patients were divided into three groups: background standard therapy (1 group), plasmapheresis introduction (2 group), adjunctive treatment with immunomodulator “Polioxidonium” course dose 78 mg. “Polioxidonium“ introduction into therapy of pancreonecrosis demonstrated not only immunomodulatory effect but also antiradical desintoxic that resulted in reduction of the number of suppurative complications and lethality.